Origin Determination and Differentiation of Gelatin Species of Bovine, Porcine, and Piscine through Analytical Methods - Hatice Saadiye Eryılmaz; Beyza Şükran Işık; Evren Demircan; Zahide Memeli; Esra Çapanoğlu; Dilara Nilüfer Erdil (Turkish Journal of Agriculture: Food Science and Technology)
Gelatin origin determination has been a crucial issue with respect to religion and health concerns. It is necessary to analyze the origin of gelatin with reliable methods to ensure not only consumer choices but also safety and legal requirements such as labeling. There are many analytical methods developed for detection and/or quantification of gelatin from different sources including bovine, porcine and piscine. These analytical methods can be divided into physicochemical, chromatographic, immunochemical, spectroscopic and molecular methods. Moreover, computational methods have been used in some cases consecutively to ensure sensitivity of the analytical methods. Every method has different advantages and limitations due to their own principles, applied food matrix and process conditions of material. The present review intends to give insight into novel analytical methods and perspectives that have been developed to differentiate porcine, bovine and piscine gelatins and to establish their authenticity. Almost every method can be succeeded in origin determination; however, it is a matter of sensitivity in that some researches fail to ensure sufficient differentiation.